UNGOVERNED OR ANTI-GOVERNANCE? HOW BITCOIN THREATENS THE FUTURE OF WESTERN INSTITUTIONS. - O'Sullivan, Andrea (Journal of International Affairs)
As the value of bitcoins cannot be strategically manipulated by an issuer to affect trade and production, Bitcoin is attractive as a store of value. It may therefore impact the future of state currencies, particularly the US dollar, as safe havens and even as reserve currencies. Furthermore, Bitcoin allows individuals to transfer value independently of established monetary and trade controls. It may therefore undermine dominant methods of controlling social behaviors by controlling financial behaviors, such as capital controls and prohibitions against money laundering.